Analisis Sikap Judgemental Antar Perempuan Melalui Perspektif Internalized Misogyny : Studi Kasus Gerbong Kereta Khusus Perempuan - Rismi Arkiani; Fany N. R. Hakim (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the phenomenon of judgmental attitudes among women in public spaces, particularly in women-only train carriages, through the perspective of radical feminism and the concept of internalized misogyny. Internalized misogyny is a form of internalization of sexist and discriminatory values ​​against women that are accepted and carried out by women themselves without realizing it, as a result of the influence of patriarchal culture that has taken root in society. This judgmental attitude appears in the form of rivalry, mutual demeaning, and the tendency to compare oneself with other women to gain validation or feel superior. A case study conducted in a women-only train carriage shows that spaces that should be safe for women actually create new social dynamics, such as competition for facilities, conflicts between passengers, and the erosion of empathy and solidarity among women. These findings indicate that internalized misogyny exacerbates negative stereotypes against women and strengthens rivalries between them, thus creating an environment that does not support solidarity. For example, women tend to demean each other or feel threatened when they are in spaces that should be safe for them. This research highlights the importance of understanding the mechanisms of internalized misogyny and its impact on women's social interactions in public spaces, as this phenomenon hinders the creation of more equal and supportive relationships between women. A deeper understanding of these dynamics can facilitate women's empowerment and foster stronger solidarity within society. Therefore, it is crucial for women to dismantle their internalized patriarchal values to foster equality and support among women in public spaces.